Bacteria Challenge in Smoke-exposed Mice Exacerbates Inflammation and Skews the Inflammatory Profile - Gaschler, Gordon J; Skrtic, Marko; Zavitz, Caleb C. J; Lindahl, Maria; Onnervik, Per-Ola; Murphy, Timothy F; Sethi, Sanjay; Stampfli, Martin R (American journal of respiratory and critical care medicine, 2009)
The pathogenesis of chronic obstructive pulmonary disease is associated with acute episodes of bacterial exacerbations. The most commonly isolated bacteria during episodes of exacerbation is nontypeable Haemophilus influenzae (NTHI). In this study, we investigated the in vivo consequences of cigarette smoke exposure on the inflammatory response to an NTHI challenge. C57BL/6 and BALB/c mice were exposed to cigarette smoke for 8 weeks and subsequently challenged intranasally with NTHI. We observed increased pulmonary inflammation and lung damage in cigarette smoke-exposed NTHI-challenged mice as compared with control NTHI-challenged mice. Furthermore, although NTHI challenge in control mice was marked by increases in tumor necrosis factor-alpha, IL-6, MIP-2, and KC/GROalpha, NTHI challenge in cigarette smoke-exposed mice led to a prominent up-regulation of a different subset of inflammatory mediators, most notably MCP-1, -3, and -5, IP-10, and MIP-1gamma. This skewed inflammatory mediator expression was also observed after ex vivo NTHI stimulation of alveolar macrophages, signifying their importance to this altered response. Importantly, corticosteroids attenuated inflammation after NTHI challenge in both cigarette smoke-exposed and control mice; however, this was associated with significantly increased bacterial burden. Collectively, these data suggest that cigarette smoke exacerbates the inflammatory response to a bacterial challenge via skewed inflammatory mediator expression.